Hepatitis C infection: challenges in dental management and diagnosis of extrahepatic manifestations - Kanno, Cláudia Misue; Castro, Alvimar Lima de; Crivelini, Marcelo Macedo (Journal of Oral Diagnosis, 2016)
Hepatitis C is associated with autoimmune diseases, hepatocellular carcinoma, and extrahepatic manifestations that, in conjunction, may seriously compromise the patient’s quality of life. We herein describe a case of chronic hepatitis C with oral manifestations and discuss some implications for diagnosis and treatment. A 63-year-old woman complaining of spontaneous bleeding of the oral mucosa presented with bilateral asymmetric ulcers surrounded by white papules and striae on the buccal mucosa. Her medical history revealed leucopenia, thrombocytopenia, and skin lesions associated with chronic hepatitis C. Propranolol and ranitidine had recently been prescribed. Lichen planus, lichenoid reaction, and erythema multiforme were considered in the differential diagnosis. Histopathological analysis revealed lymphocytic infiltrate in a lichenoid pattern. The lesions partially healed after 1 week and completely regressed after 6 months, despite the maintenance of all medicaions; no recurrence was observed. The final diagnosis was oral lichen planus associated with hepatitis C. Chronic hepatitis C may present oral manifestations, which demand adjustments in dental treatment planning. Medication side effects may interfere with the clinical presentation and course of the disease and should be accounted for in the differential diagnosis. The possibility of spontaneous remission of oral lichen planus should always be considered, especially when putative etiological factors of a lichenoid lesion are withdrawn in an attempt to differentiate oral lichen planus from lichenoid lesions. This case emphasizes the importance of recognizing the extrahepatic manifestations of hepatitis C as a cause of increased morbidity.